2013
DOI: 10.3892/etm.2013.1190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cilostazol versus ticlopidine following coronary stenting in patients with coronary heart disease: A meta-analysis of randomized controlled trials

Abstract: Previous studies have shown that the combination of cilostazol and aspirin may be a more effective regimen than ticlopidine plus aspirin in the prevention of late restenosis and acute or subacute stent thrombosis following coronary stenting; however, individually published results are inconclusive. The aim of this meta-analysis was to compare the differences in late restenosis and stent thrombosis between cilostazol plus aspirin and ticlopidine plus aspirin for patients with coronary heart disease (CHD) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A meta‐analysis of 12 RCTs comprising 2708 patients with CAD following coronary stenting indicated that cilostazol plus aspirin (n = 1371) conferred a reduced restenosis rate (OR, 0.83; P = .047) and a lower mean percent diameter stenosis than ticlopidine plus aspirin (n = 1337; P = .001) 143 . However, the rates of acute or subacute stent thrombosis were not significantly different between cilostazol plus aspirin and ticlopidine plus aspirin.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…A meta‐analysis of 12 RCTs comprising 2708 patients with CAD following coronary stenting indicated that cilostazol plus aspirin (n = 1371) conferred a reduced restenosis rate (OR, 0.83; P = .047) and a lower mean percent diameter stenosis than ticlopidine plus aspirin (n = 1337; P = .001) 143 . However, the rates of acute or subacute stent thrombosis were not significantly different between cilostazol plus aspirin and ticlopidine plus aspirin.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Although many efforts have recently been introduced to improve people's health in China, the vast territory and unbalanced economic development have limited these efforts, especially in patients with cardiovascular disease [1][2][3]. As one of the most serious diseases threatening human health, coronary heart disease (CHD) consumes vast medical resources [4,5]. One of the key treatments for CHD is percutaneous transluminal coronary intervention (PCI), however, this treatment is costly because of the expensive stents and balloons used for this procedure, which imposes a high financial burden for patients and society.…”
Section: Introductionmentioning
confidence: 99%